NASCIMENTO MORAES, UM NARRADOR DOS SUBALTERNOS: Interpretações acerca da Alteridade, (Des)igualdade e 'Diferença' em São Luís do Pós- abolição e início da República (c. 1880-1915) - LIMA, Claudia Silva (2023)
The thesis titled NASCIMENTO MORAES, A NARRATOR OF THE SUBALTERNS: Interpretations of Alterity, (In)equality, and 'Difference' in São Luís during the Post- Abolition and Early Republic (c. 1880-1915), aims to understand the social and historical perspective expressed by Nascimento Moraes in "Vencidos e Degenerados" (1910). The study focuses on the representation of alterity, inequality, and difference among the subalterns in São Luís during the post-abolition and early republic phase. It seeks to comprehend how, during the transition from the 19th to the 20th century, Nascimento Moraes wrote about the lives of the subalterns of his time, particularly black and mestizo individuals, including freed slaves, impoverished freemen, laborers, and subaltern intellectuals. The goal is to provide discursive and historical visibility to these marginalized individuals due to the continuous structuring of coloniality. Methodologically, the analysis of the novel is conducted within the intersection of history and literature, from a perspective of literary and discursive criticism. The epistemological approach is grounded in the reflections of de(s) coloniality theorists, such as Fanon (2008), Mbembe (2001; 2014; 2017), Spivak (2010), Mignolo (2003), Quijano (2000; 2005; 2009), and Dussel (1993). All of these thinkers adopt a critical stance towards the Eurocentrism of coloniality, focusing on issues of alterity, inequality, and difference, arising from the epistemologies that emerge from the scars of the histories, experiences, and memories of the colonized. In this panorama, Nascimento Moraes challenged the modern colonial imaginary. His work "Vencidos e Degenerados" goes beyond mere literature; it represents an act of historical justice, proposing a shift away from colonial narratives in historical reinterpretation, particularly by giving voice to individuals who were denied the right to narrate, resist, and fight for their "existence." Nascimento Moraes's work is a call for social, ethical, and human reconfiguration, emphasizing the need to consider alterity and combat the violent structuring of inequality and difference in the social and cultural fabric of Ludovicense society. His libertarian writing is situated in a new epistemic locus of ontological enunciation, a liminal gnosis, with the aim of self- inscription, of the other, and of the world. This is intended to ensure that spaces of discourse linked to just processes of citizen emancipation are truly inscribed in the history of São Luís.